(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Arterial hypertension remains a leading cause of global cardiovascular morbidity and mortality, with its pathogenesis involving complex multifactorial mechanisms. The vascular endothelium, once regarded as a simple anatomical barrier, is now recognized as a dynamic endocrine organ that critically regulates vascular homeostasis. Endothelial dysfunction represents a pivotal early event in the development and progression of arterial hypertension, characterized by impaired endothelium-dependent vasodilation, reduced nitric oxide bioavailability, and a shift towards a proinflammatory and prothrombotic phenotype. This review examines the molecular mechanisms linking endothelial dysfunction to hypertension, including oxidative stress, uncoupling of endothelial nitric oxide synthase, imbalance between vasodilators and vasoconstrictors, and inflammatory pathway activation. We discuss current evidence from clinical and experimental studies demonstrating that endothelial dysfunction not only precedes the clinical manifestation of hypertension but also contributes to target organ damage. Furthermore, we evaluate diagnostic approaches for assessing endothelial function and explore therapeutic strategies targeting the endothelium. Understanding the complex bidirectional relationship between endothelial dysfunction and hypertension is essential for developing personalized prevention and treatment strategies.